Improvement of Operative Treatment of Chronic Dislocation of the Shoulder Joint - oʻgʻli, Raxmonov Shoximordon Sherqul (American Journal of Biomedicine and Pharmacy, 2025)
Chronic dislocation of the shoulder joint is one of the most challenging orthopedic conditions, often resulting from repeated trauma or unsuccessful primary treatment of acute dislocation. The complexity of this pathology lies in soft tissue contractures, bone defects, and capsular insufficiency, which make reduction and stabilization difficult. This study focuses on improving surgical approaches to achieve optimal stability and functional recovery of the shoulder joint in chronic cases. By comparing traditional open reduction and modern reconstructive techniques, the study evaluates the effectiveness of different surgical interventions, aiming to develop a standardized operative protocol for better outcomes. Chronic shoulder dislocation represents one of the most complex and disabling pathologies in orthopedic practice. It often results from neglected acute dislocation or repeated traumatic episodes that gradually destroy the normal anatomy and function of the shoulder joint. Long-term dislocation leads to contracture of the periarticular soft tissues, atrophy of rotator cuff muscles, and significant degenerative changes in the glenoid and humeral head. The study aims to evaluate and improve the surgical management of chronic shoulder dislocation by introducing modified techniques that provide stronger stabilization, reduced recurrence, and enhanced shoulder mobility. The focus is placed on comparative analysis between classical open reduction with capsule-ligament reconstruction and advanced bone-grafting methods such as the modified Latarjet procedure.